1981
DOI: 10.1088/0031-9155/26/1/002
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of lens material at microwave frequencies

Abstract: Values of the complex permittivity of human and rabbit lens material in the frequency range 100--6000 MHz are reported. The data were obtained by using an on-line computer-based time-domain spectrometer. The lenses were divided into an outer (cortical) zone and an inner (nuclear) zone and the dielectric properties of each zone were measured separately for both species of lens. The results are analysed in terms of the aqueous and protein constituents, assuming a molecular model whereby the hydrated protein mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Moreover this difference is increasing as the frequency decreases. The rapid fall in relative permittivity (e') with frequency up to around 100 MHz is known (Schwan & Foster, 1980;Grant et al, 1978) to be a property of the cell membranes and has been observed in other biological tissues such as brain (Nightingale et al, 1980) and lens (Dawkins et al, 1981a). For all tissues, including the mouse muscle investigated in the present work, the data between about 50 and about 500 MHz correspond to the high frequency tail of the ^-dispersion.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover this difference is increasing as the frequency decreases. The rapid fall in relative permittivity (e') with frequency up to around 100 MHz is known (Schwan & Foster, 1980;Grant et al, 1978) to be a property of the cell membranes and has been observed in other biological tissues such as brain (Nightingale et al, 1980) and lens (Dawkins et al, 1981a). For all tissues, including the mouse muscle investigated in the present work, the data between about 50 and about 500 MHz correspond to the high frequency tail of the ^-dispersion.…”
Section: Discussionmentioning
confidence: 99%
“…The model parameters for porcine cornea from Table 1 are used to provide comparison with a recent set of cornea data [34] measured and reported for three age-groups of pigs over the 0.4-10 GHz frequency range. In accordance with the measurement procedures [35] which correspond to the parallel electric field polarization for the cornea, comparison is presented for ε cor in Figure 4 and in the rest of the paper. The model shows agreement with the experimental data within the usual experimental tolerance of 20%.…”
Section: Resultsmentioning
confidence: 99%
“…In previous publications (Dawkins et al 1981a, Gabriel et a1 1983 measurements have been reported on the dielectric parameters of various ocular tissues at 37 "C. In the present work dielectric data on three tissues-retina, lens cortex and lens nucleus-are presented over a temperature range. It was hoped that varying the temperature would provide additional information which would further our research concerned with studying the nature of water in biological material.…”
Section: Introductionmentioning
confidence: 79%